Visual impairment in pseudoexfoliation from four tertiary centres in India - Rao, Aparna; Raj, Niranjan; Pradhan, Amiya; Senthil, Sirisha; Garudadri, Chandra S.; Verma, P. V. K. S; Gupta, Prakriti (PloS one, 2020)
To analyse the disease burden of pseudoexfoliation (PXF) disease stages from East and South India. Prospective hospital based study of patients seen at 4 tertiary centres. Consecutive old and new patients of pseudoexfoliation with normal intraocular pressure (IOP), raised IOP (PXF with Ocular hypertension, OHT) and irreversible disc/field changes (pseudoexfoliation glaucoma, PXG) seen from April 2016-March 2017 at a tertiary centre in Odisha, East India and 3 centres in Andhra Pradesh and Telangana, South India, recruited into the prospective study were screened for baseline characteristics. The clinical and demographic details including visual acuity, laterality, intraocular pressure (IOP) with details of medical/surgical therapy at presentation were collected from the hospital database at all 4 centres. The World Health Organization WHO visual criteria were used for defining visual impairment/absolute blindness in different disease stages. The visual impairment/blindness rates with comorbidities in the anterior/posterior segment in PXF, OHT and PXG at baseline were compared and the influence of age, IOP fluctuations and laterality was analysed using multivariate logistic regression. Of 6284 PXF eyes (of 3142 patients) included from all centres, OHT and PXG was seen in 2.1% and 29% respectively which included 3676 (>50%) bilateral PXF eyes. Reversible visual impairment rates caused by PXF associated co-morbidities in PXF and OHT were 33% and 26% respectively with cataract being the major cause (67% in PXF and 74% in OHT). Irreversible blindness rate was higher in bilateral PXG eyes (30.5%) compared to bilateral PXF (23.2%) or bilateral OHT (21.6%) with overall absolute blindness rates of 28.2% at presentation. Older age (p<0.001), bilaterality and higher baseline IOP were significantly associated with higher rates of blindness in PXF eyes. Pseudoexfoliation is associated with ≥30% visual impairment across all stages and 28% absolute blindness rate which is a huge hidden burden of glaucoma. Adequate disease staging and assessment of comorbidities is required for accurate prognostication at baseline and reducing avoidable pseudoexfoliation blindness.